Frequency of types of parturition and their relationship with maternal characteristics: a cross-sectional analysis - Khan, Farah; Jamshed, Saira; Bano, Zakia; Begum, Amna; Ariff, Madiha; Anwar, Adnan (International Journal of Research in Medical Sciences, 2020)
Background: The pathways that are involved for the duration of pregnancy and type of parturition are extremely complex, involving maternal as well as fetal systems. The objective of this study was to determine the frequency of types of parturition and their relationship with maternal characteristics among pregnant female patients. Methods: A cross-sectional survey using a non-probability convenient sampling technique was conducted among 195 healthy pregnant females at Obstetrics and Gynaecological Department of Hamdard Hospital, Karachi, from 1st March 2019 to 31st August 2019. After taking written informed consent from the participants, the relevant data were gathered with the help of a structured questionnaire designed specifically for the study. Statistical package for social sciences was used for data entry while the chi-square test was applied for inferential analysis. The duration of the study was six months. Data were entered and analyzed using Statistical Package for Social Sciences version 20.0. Descriptive analysis was performed by generating means and standard deviations for continuous variables while frequencies and percentages for categorical variables. A Chi-square test was applied to perform the inferential analysis while the significance level was set at 0.05. Results: A total of 195 pregnant females were included in the study, whose mean age was 29.29±5.22 years. The study results showed that BMI before pregnancy (p=0.021), rest is taken during pregnancy (p=0.034) and gravida status (p=0.047) were all significantly associated with the type of parturition among the study participants, but spacing in pregnancies and parity were not. Conclusions: Maternal characteristics were found to be significantly associated with the type of parturition among pregnant females. For gynecologists the maternal characteristics identified in this study may serve as a useful indicator of the type of parturition expected in their patients.